Accra statement for a food-secure Africa - Bioversity International (2014)
The 3rd International Conference on Neglected and underutilized species (NUS) – for a food-secure Africa, was held in Accra, Ghana in September 2013. Three conference themes – Resilience of agricultural and livelihood systems; Value chains, and; Creating an enabling policy environment – highlighted that neglected and underutilized species are important to tackling poverty, malnutrition and climate change, and to seizing new opportunities for agricultural growth. Drawing on scientific presentations and a policy panel discussion, the Accra statement sets out nine policy recommendations for realizing the promise of these valuable species.